PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER ( NHT ) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 015 BINSUS KEC. DUMAI TIMUR - Mega Lingga Wati Lingga Wati; Gustimal Witri Witri; Hendri Marhadi Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : A problem in this research is the low result a student of grade III learning Science primary school of 015 Binsus Kec. Dumai Timur average score early 60,4 This research aims to increase Science of  III grade SD 015 Binsus Kec. Dumai Timur through "implementation coooperative learing numbered head together )".  Instrument data collection on final project is test student performance, sheets observation such teachers and sheets observation students' activity. This research conducted in march to april 2014 that was carried out as much as 2 cycle.subjects this research is a grade III grade 015 Binsus Kec. Dumai Timur elementary school 25 students. Such teachers cycle I first meeting with the percentage 62,5 percent with the category enough, increased at cycle I meeting II with the percentage 65,6 percent were categorized as enough, then, the increase in the cycle II first meeting with the percentage 78,12 percent were categorized as it was good, and in a meeting between the two cycle II with a percentage 87,5 percent were categorized as it was very good. While such students in the cycle I meeting I on the percentage 53,57percent with the category is increased at cycle I meeting II percentage 60,71 percent with the category. At cycle II meeting I percentage 71,42 percent with the category amamt both experienced an increase in the cycle II meeting II with the percentage 85,71 percent were categorized as it is very good. Average learning experience an increase from the score basis. Average value - average scores basic 60,4 increased at cycle I with the average 65,6and in the cycle II, the increase to 79. The percentage the increase learning outcomes from the score the basic to life span I reached 4.96 percent and from the score the basic to life span II, the increase of 10.73 percent, With the percentage thoroughness reached 83.33 percent and was declared to be completed. From this research can be concluded that with The implementation approach they cooperative learning type numbered head together can Improve Learning Science Students in grade III 015 Binsus Kec. Dumai Timur . Key words : Cooperative learning type Numbered Head Together ( NHT ), result science